(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Purpose: To assess the safety, efficacy and complications using 23-gauge vitrectomy system. Method: 34 patients that underwent 23-G transconjunctival sutureless vitrectomy technique were included in the study. All patients were operated by a single surgeon at a single centre. Common indications for surgery were rhegmatogenous retinal detachment, diabetic vitreous hemorrhage with no tractional retinal detachment, diabetic vitreous hemorrhage with tractional retinal detachment and phacoemulsification with vitreous hemorrhage. Results: Good instrumentation made it possible to apply most of the standard procedure with exception of high molecular weight silicone oil (5000 cst). The average operating time was 48 minutes. Time was saved in beginning (peritomy securing of sclerotomy ports) and end of procedure (suturing the sclera and conjunctival wound). No scleral port required suturing at the end of procedure. Silicone oil (1000cst) was filled for internal tamponade where needed. Scanty leakage of silicone oil was seen in 6 (17.6%) eyes from one of the ports which stopped within 24-48hours causing no ocular complications. Localized conjunctival hemorrhage appeared in 8 (23.5%) eyes from pull of cannulas causing bleed from sclera ports or episcleral vessels. Recurrent (mild) vitreous hemorrhage was seen in 4 eyes (11.7%). Visual acuity improved postoperatively in 18 (52.9%) eyes, unchanged in 12 (35.5%) eyes and decreased in 4 (11.8%) eyes. Postoperative hypotony (IOP 8mmHg or less) occurred in 14 (41.2%) eyes on day 1 which returned to normal range within 24-48 hours without any complications. No other complications like choroidal detachment, endophthalmitis etc were seen in 3 months follow-up. Conclusion: 23-gauge transconjunctival sutureless vitrectomy is a safe surgical technique. It reduces surgical time and allows faster wound healing, diminished conjunctival scarring, improved patient comfort and decreased post-operative inflammation. It is suitable for a large number of indications.